2019
DOI: 10.1111/joa.12952
|View full text |Cite
|
Sign up to set email alerts
|

The bizarre skull of Xenotyphlops sheds light on synapomorphies of Typhlopoidea

Abstract: The emerging picture of non-monophyly of scolecophidian snakes is increasingly indicative that fossorial lifestyle, myrmecophagous diet, and miniaturisation are powerful drivers of morphological evolution in squamate skulls. We provide a detailed description of the skull of Xenotyphlops grandidieri, with reference to the skulls of other scolecophidian snakes. The skull, which shows dramatic ventral inflection of the snout complex, is remarkably bizarre, and the mouth opening is more ventrally oriented than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(69 citation statements)
references
References 48 publications
5
64
0
Order By: Relevance
“…This sample size is consistent with that used in other micro-CT-related studies of snake morphology (e.g. see [6,16]).…”
Section: Methodssupporting
confidence: 85%
“…This sample size is consistent with that used in other micro-CT-related studies of snake morphology (e.g. see [6,16]).…”
Section: Methodssupporting
confidence: 85%
“…In fact, the paedomorphosis exhibited by scolecophidians is in many ways comparable to that of Atractaspis —e.g., the reduced mandible and highly reduced and often absent dentition (Kley, 2006; Caldwell, 2019)—though in other aspects it is far more extensive than that noted herein for Atractaspis (Figure 11). For example, the proximal epiphysis of the quadrate remains unfused (Kley, 2006), the ectopterygoid and supratemporal are typically completely absent or at least extremely reduced (Rieppel et al , 2009; Caldwell, 2019; Chretien et al , 2019), and the quadrate is oriented anteriorly, representing an extreme retention of the embryonic squamate condition (Kamal, 1966; Rieppel and Zaher, 2000; Kley, 2006; Hernández‐Jaimes et al , 2012; Scanferla, 2016; Caldwell, 2019). Similar reduction and anterior displacement of the suspensorium occurs in other miniaturized snakes, such as Anomochilus and Uropeltis (Sections 3.5.1 and 3.5.2; see also Olori and Bell, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although a robust phylogenetic context is still lacking for snakes (Chretien et al , 2019), recently revised and large‐scale datasets such as that of Simões et al (2018) and Garberoglio et al (2019) provide a sound basis for future large‐scale studies of snake evolution. Interestingly, a recent morphological phylogeny (Garberoglio et al , 2019) focussing on extinct snakes recovered scolecophidians as nested within Alethinophidia (Figure 12b), in stark contrast to the more orthodox placement of this group as basally divergent among Serpentes (Figure 12a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no fossil cranial remains have ever been found and, frustratingly, their vertebral anatomy is so conservative and similar among taxa that it does not permit distinguishing diagnostic taxonomic features. This taxonomic problem should be mostly attributed to the unfortunate fact that only few studies have dealt with the skeletal anatomy of extant scolecophidians, and that the rare studies focused on cranial features (e.g., List, 1966;Rieppel, 1979;Kraus, 2017;Chretien et al, 2019). As such, the two distinct scolecophidian clades that currently inhabit the northeastern Mediterranean, i.e., Typhlopidae (genera Letheobia Cope, 1869, andXerotyphlops Hedges, Marion, Lipp, Marin, andVidal, 2014), and Leptotyphlopidae (genus Myriop-holis Hedges, Adalsteinsson, and Branch in Adalsteinsson et al, 2009) cannot be reliably identified in the European fossil record.…”
Section: Diversity Affinities and Palaeobiogeography Of The Maramenmentioning
confidence: 99%